The effectiveness of the different styles of video clips through flipped classrooms in developing the Tajweed skills of primary school students - Alsulami, Nasser Aali (Journal of Educational and Psychological Sciences, 2020)
The aim of the research was to identify the effectiveness of the different styles of video clips through flipped classrooms in developing the Tajweed skills of primary school students. The semi-experimental method was used to suit the nature of the research. The sample consisted of 50 students from the fifth-grade primary school of Abdullah bin Tariq Primary School. They were divided into two groups: the first group where a video style was used with a text equivalent, and in the second group a non-linear video pattern was used with a text equivalent across the inverted chapters. To test the validity of the hypothesis, the T-test was used by the SPSS. The results of the study indicated that there were no statistically significant differences between (0.05) between the average scores of the experimental groups in the test and the observation card due to the difference in the pattern of the videos/ Unaccompanied) text equivalent.Based on the findings of the research, the researcher recommended the use of the different style of videos through different chapters in the teaching of other subjects, and encourage teachers and educators to use educational videos through the flipped learning because of their impact on the development of skills and raise the level of achievement.
Keywords: inverted learning; instructional video; text equivalent